Apolipoprotein Aβ: Black Sheep in a Good Family - Kontush, Anatol (Brain Pathol, 2006)
Amyloid‐β (Aβ) has for a long time been thought to play a central role in the pathogenesis of Alzheimer disease (AD). Analysis of available data indicates that Aβ possesses properties of a metal‐binding apolipoprotein influencing lipid transport and metabolism. Protection of lipoproteins from oxidation by transition metals, synaptic activity and role in the acute phase response represent plausible physiological functions of Aβ. However, these important biochemical qualities which may critically influence the development of AD, have been largely ignored by mainstream AD researchers, making Aβ appear to be a “black sheep” in a “good apolipoprotein” family. New studies are needed to shed further light on the physiological role of Aβ in lipid metabolism in the brain.